Investigation of Velocity Control System with Programmable Variable Structure Controller - Šulčius, N; Geleževičius, V. A. (Elektronika ir Elektrotechnika, 2007)
The velocity control system with programmable variable structure velocity controller is developed and investigated. The programmable device defines P control law interval time in dependence on the static load level of the system. The static load current estimation is performed by the designed Luenberger observer. The derived static load current signal is suitable for use in the P control law interval time definition device. The input-output dependence of the programmable device is developed ensuring optimal dynamical quality of the velocity control system independently on the static load conditions. The presented simulations results of the velocity control system using programmable variable structure controller coincide with analogical results obtained applying Fuzzy logic based variable structure controller. Ill. 5, bibl. 5 (in English; summaries in English, Russian and Lithuanian).